Genetic deletion of 12/15 lipoxygenase promotes effective resolution of inflammation following myocardial infarction. (May 2018) - Kain, Vasundhara; Ingle, Kevin A.; Kabarowski, Janusz; Barnes, Stephen; Limdi, Nita A.; Prabhu, Sumanth D.; Halade, Ganesh V.
Abstract: 12/15 lipoxygenase (LOX) directs inflammation and lipid remodeling. However, the role of 12/15LOX in post-myocardial infarction (MI) left ventricular remodeling is unclear. To determine the role of 12/15LOX, 8–12 week-old C57BL/6 J wild-type (WT; n = 93) and 12/15LOX −/− (n = 97) mice were subjected to permanent coronary artery ligation and monitored at day (d)1 and d5 post-operatively. Post-MI d28 survival was measured in male and female mice. No-MI surgery mice were maintained as d0 naïve controls. 12/15LOX −/− mice exhibited higher survival rates with lower cardiac rupture and improved LV function as compared with WT post-MI. Compared to WT, neutrophils and macrophages in 12/15LOX −/− mice were polarized towards N2 and M2 phenotypes, respectively, with increased of expression mrc-1, ym-1, and arg -1 post-MI. 12/15LOX −/− mice exhibited lower levels of pro-inflammatory 12-(S)-hydroperoxyeicosatetraenoic acid (12(S)-HETE) and higher CYP2J-derived epoxyeicosatrienoic acids (EETs) levels. CYP2J-derived 5, 6-, 8, 9-, 11, 12-, and 14, 15-EETs activated macrophage-specific hemeoxygenase (HO)-1 marked with increases in F4/80 + /Ly6C low and F4/80 + /CD206 high cells at d5 post-MI in 12/15LOX −/− mice. In contrast, inhibition of HO-1 led to total mortality in 12/15LOX −/− mice by post-MI d5. 12/15LOX −/− mice exhibited reduced collagen density and lower α-smooth muscle actin (SMA) expression at d5 post-MI, indicating delayed or limited fibroblast-to-myofibroblast differentiation. In conclusion, genetic deletion of 12/15LOX reduces 12(S)-HETE and activates CYP2J-derived EETs to promote effective resolution of inflammation post-MI leading to reduced cardiac rupture, improved LV function, and better survival. Graphical abstract: Highlights: 12/15LOX deletion improved post-MI survival by reducing cardiac rupture and ameliorated cardiac function. 12/15LOX deletion accelerated inflammation resolution by promoting neutrophil and macrophage polarization post-MI. 12/15LOX deletion increased CYP2J-derived proresolving epoxyeicosatrienoic acid (EETs) thereby limited cardiac remodeling.